The Consultative Group on International Agricultural Research (CGIAR) Micronutrients Project: justification and objectives - Bouis, Howarth E.; Graham, Robin D.; Welch, Ross M. (United Nations University, 2000)
The general objective of the Consultative Group on International Agricultural Research (CGIAR) Micronutrients Project is to assemble the package of tools that plant breeders will need to produce mineral- and vitamin-dense cultivars. The target crops are rice, wheat, maize, phaseolus beans, and cassava. The target micronutrients are iron, zinc, and vitamin A. The combining of benefits for human nutrition and agricultural productivity, resulting from breeding staple food crops that are more efficient in the uptake of trace minerals from the soil and that load more trace minerals into their seeds, results in extremely high ex ante estimates of benefit–cost ratios for investments in agricultural research in this area. This finding derives from the confluence of several complementary factors. The rates of micronutrient malnutrition are high, as are the consequent costs to human welfare and economic productivity. High trace mineral density in seeds produces more viable and vigorous seedlings, and efficiency in the uptake of trace minerals improves disease resistance. Trace-mineral-“deficient” soils in fact contain high amounts of trace minerals that are “unavailable” to staple crop varieties presently grown. Adoption of nutritionally improved varieties by farmers can rely on profit incentives; delivery to consumers can rely on existing demand behaviour. Relatively small investments in agricultural research at a central research location may be disseminated widely. Breeding advances are derived from initial, fixed costs, with low recurring costs. The encouraging research results obtained to date under the project would seem to justify a much expanded effort in the future.